An introduction to EU competition law - Lorenz, Moritz (Cambridge University Press, 2013)
"Section on the Economic Foundations of EU competition law contributed by Julia Dietrich."; Includes bibliographical references and index.; Economic and legal foundations of EU competition law -- Key concepts of Article 101 TFEU -- Possibilities for cooperation under Article 101 TFEU -- Article 102 TFEU : abuse of a dominant position -- Merger control -- Cartels.